Analisis Perubahan Lahan Sawah Berbasis Sistem Informasi Geografis di Wilayah Perkotaan Pangkajene Kabupaten Sidenreng Rappang - Reza Asra; Andi Ayu Nurnawati; Muh. Irwan; Muh. Faisal Mappiasse (Fapetrik-UMPAR, 2020)
The conversion of agricultural land at a high enough rate may threaten the food security of the population. The agricultural land most vulnerable to conversion is the rice field. The aim of this study was to determine the changes in paddy fields from 2013 to 2020, the distribution of the transformation of paddy fields to other lands, and the factors that influence the conversion of paddy fields. This research was carried out by digitizing the on-screen image method in 2013 and 2020. The classification of land use results from digitization was tested for accuracy by determining the sample points in the GIS (Geographic Information System) application and then compared to the results of the field survey. In addition, an analysis of the changes in paddy fields was carried out by overlaying land use maps in 2013 and 2020. Observations and interviews with people whose land was changing were conducted on the factors affecting the change in paddy fields. Changes in land use over a period of 7 years (2013-2020), namely rice fields, decreased by 149 ha (7.36 percent ). Meanwhile, there has been an increase in the area in other land uses. The function of the paddy fields in the urban area of Pangkajene, Sidrap Regency, has become 18.69 hectares of land built, 59.42 hectares of mixed gardens, 23.13 hectares of open/empty land and 49.11 hectares of land. The factor that affects the conversion of paddy fields in the urban area of Pangkajene is the strategic location of the land, which causes the community to convert its land into a place of trade and services. The increase in the number of people requiring large land areas has led to the construction of many residential complexes in rice fields and the high selling price of rice fields, which encourages farmers to sell their land.